COLORIMETRIC VS. CHROMATOGRAPHIC ANALYSES OF ALKALOIDS IN LUPIN SEEDS - Wilczura, Paulina; Święcicki, Wojciech; Kamel, Katarzyna; Wasiak, Wiesław (Plant Breeding and Seed Science, 2018)
A characteristic trait of lupins is a production of alkaloids, which are a toxic and bitter taste compound of seeds. Due to the lack of fast, sensitive and inexpensive screening techniques to identify and reject high alkaloid plant material, development of suitable tools is important challenges for lupins breeding and seed production. The aim of this study was to compare two alkaloid content estimation methods in Lupinus angustifolius L. and Lupinus albus L. During the Wagner’s colorimetric test, which is recommended by the UPOV, seed halves were stained on four colors depending on the alkaloid content but only the level of 0.5% – 0.6% showed clear color change. Gas chromatography allowed accurate quantification and qualification of alkaloid content. Since safe alkaloid content for consumption is 0.02% of seed dry weight, colorimetric method is less useful for dividing lupin cultivars into sweet and bitter, than gas chromatography but can be used as a screening technique.